Continentalizing Canada : the Politics and Legacy of the Macdonald Royal Commission. - Inwood, Gregory J. (Studies in comparative political economy and public policy., 2005)
Accessible to readers interested in Canadian politics, policy, or economy, Continentalizing Canada offers a thorough examination into the Macdonald Commission and the resulting discourse in the Canadian political economy.